Pitquhivut Ilihaqtavut (“Learning about Our Culture”): A Collaborative Approach to Archaeology and Traditional Knowledge in Inuit Nunangat - Friesen, Max; Angulalik, Emily; Crockatt, Kim; Hakongak Gross, Pamela; Angulalik, Gwen (Études Inuit Studies, 2022)
This paper describes a long-term collaboration between the Pitquhirnikkut Ilihautiniq/Kitikmeot Heritage Society (PI/KHS) of Cambridge Bay, Nunavut and the University of Toronto. The PI/KHS is a very active, Elder-run organization with activities ranging across oral history, traditional knowledge, language, place names, school programs, and the running of a museum. They have been collaborating with archaeologists from the University of Toronto since 1999 to expand their programming, learn more about very early time periods in their region, and provide additional opportunities to record traditional knowledge and involve Inuit youth in heritage programming. We discuss the history of this collaboration and its practical organizational aspects, and we conclude with thoughts on why it continues to work after over 20 years.